From Siblings to Cousins Prospering in the Third Generation and Beyond - Aronoff, C. (A Family Business Publication, 2011)
Here Aronoff and Ward show siblings and cousins how to work together on key issues that are critical to the future success of the business including how to attract the most capable family members into leadership roles, how to develop agreement among many owners and how to create a "cousin collaboration".